National parks in the eastern United States harbor important older forest structure compared with matrix forests. Issue 7 (20th July 2016) - Miller, Kathryn M.; Dieffenbach, Fred W.; Campbell, J. Patrick; Cass, Wendy B.; Comiskey, James A.; Matthews, Elizabeth R.; McGill, Brian J.; Mitchell, Brian R.; Perles, Stephanie J.; Sanders, Suzanne; Schmit, John Paul; Smith, Stephen; et al.
Abstract: We analyzed land‐cover and forest vegetation data from nearly 25, 000 permanent plots distributed across 50 national parks in the eastern United States, along with the matrix around each park, to examine structural characteristics of park forests in relation to their surrounding landscape. Over 2000 of these plots are part of the National Park Service (NPS) Inventory and Monitoring Program (I&M), and the remaining 22, 500+ plots are part of the US Forest Service (USFS) Forest Inventory and Analysis (FIA) Program. This is the first study to compare forest structure in protected lands with the surrounding forest matrix over such a large area of the United States and is only possible because of the 10+ years of data that are now publicly available from USFS‐FIA and NPS I&M. Results of this study indicate that park forests, where logging is largely prohibited, preserve areas of regionally significant older forest habitat. Park forests consistently had greater proportions of late‐successional forest, greater live tree basal area, greater densities of live and dead large trees, and considerably larger volume of coarse woody debris. Park forests also had lower tree growth and mortality rates than matrix forests, suggesting different forest dynamics between park and matrix forests. The divergent patterns we observed between matrix and park forests were similar to those reported in studies that compared managed and old‐growth forests, although the differences in our study were less pronounced. With the majority of park forests in second growth, eastern parks may be a more realistic baseline to compare with the more intensively managed matrix forests. We recommend that park managers allow natural disturbance and the development of older structure to continue in park forests. In addition, long‐term maintenance of regional biodiversity will likely require increases in older forest structure in the matrix. As the NPS moves into its next century of land preservation, we encourage managers to consider parks important components of a larger regional effort to preserve biodiversity and ecosystem processes in eastern US forests. The data collected by NPS I&M programs will continue to provide important information and guidance toward these regional conservation efforts.